2009
DOI: 10.1002/rcm.4109
|View full text |Cite
|
Sign up to set email alerts
|

δ13C,δ15N andδ2H isotope ratio mass spectrometry of ephedrine and pseudoephedrine: application to methylamphetamine profiling

Abstract: Conventional chemical profiling of methylamphetamine has been used for many years to determine the synthetic route employed and where possible to identify the precursor chemicals used. In this study stable isotope ratio analysis was investigated as a means of determining the origin of the methylamphetamine precursors, ephedrine and pseudoephedrine. Ephedrine and pseudoephedrine may be prepared industrially by several routes. Results are presented for the stable isotope ratios of carbon (delta(13)C), nitrogen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 43 publications
1
67
0
Order By: Relevance
“…This means that any large differences in d 15 N and d 13 C between groups of samples should be due to the use of a different sample of precursor, and this has been indicated by results of previous studies [4,5,8]. In contrast, for d 2 H, changes in reaction conditions may lead to large changes in the observed isotope ratio.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…This means that any large differences in d 15 N and d 13 C between groups of samples should be due to the use of a different sample of precursor, and this has been indicated by results of previous studies [4,5,8]. In contrast, for d 2 H, changes in reaction conditions may lead to large changes in the observed isotope ratio.…”
Section: Introductionmentioning
confidence: 69%
“…Polarimetry results (Table 3) obtained for a selection of the samples indicated that it is highly likely the samples were synthesized from (À)-ephedrine and not phenyl-2-propanone. Consequently, IRMS results for this sample set can be discussed with reference to results from isotope studies on ephedrine and on methamphetamine synthesized from ephedrine [4][5][6]. Based on hierarchical cluster analysis (Fig.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Readers may also find of interest a recent paper by Collins et al on IRMS of ephedrine and pseudoephedrine used to produce methamphetamine. [13] Finally, Niamh Nic Daeid and colleagues from the Centre for Forensic Science at the University of Strathdyde discuss the use of IRMS for forensic uses. [14] The reader is also referred to an earlier review by Benson et al [15] In conclusion, the forensic world provides almost untapped opportunities to apply chemistry in a practical and useful way.…”
Section: Louis Pasteurmentioning
confidence: 99%
“…Recently, stable isotope ratio mass spectrometry (IRMS) has been increasingly used in analysis of MA and its precursors to obtain sample-linking information, especially in cases where conventional drug profiling may fail [7][8][9][10][11][12][13]. The isotopic compositions of synthetic substances depend on isotopic variations in the raw materials and isotopic fractionation during the synthetic process.…”
Section: Introductionmentioning
confidence: 99%